Comparisons of Water-Equivalent Diameter Measured on Images of Abdominal Routine Computed Tomography with and without A Contrast Agent - A. Nitasari; C. Anam; W. S. Budi; A. L. Wati; S Syarifudin; G. Dougherty (PPIKSN-BATAN, 2021)
The size-specific dose estimate (SSDE) is a metric for an estimation of patient dose in computed tomography (CT). The SSDE strongly depends on the water-equivalent diameter (DW). In abdominal CT examinations, a contrast agent is sometimes used to more clearly visualize tissue lesions. The Hounsfield unit (HU) of CT images with and without the use of a contrast agent at specific areas is slightly different and it may affect the DW value. This study aimed to compare the DW values calculated from axial CT images in patients who had undergone routine abdominal scans both with and without the use of a contrast agent. Axial images of 144 patients with a weight range of 3.5 kg to 90 kg who had undergone routine abdominal scans both with and without the use of a contrast agent using a Siemens Sensation 64 CT scanner were retrospectively collected. The DW values were automatically calculated using the Matlab-based IndoseCT (version 15a) software. The results show the percentage difference between DW,contrast and DW,non-contrast is below 2 %.As a result, the mean SSDEcontrast is 1.5 % smaller than SSDEnon-contrast. Due to the effect of a contrast agent on the DW and SSDE values is below 2 %, the axial images of CT abdomen without the use of a contrast agent can be used as the accurate estimation of DW and SSDE for images with the use of a contrast agent.